Public perception of COVID-19 in the Triângulo Mineiro region, Minas Gerais state, Brazil: a cross-sectional survey - de Oliveira-Leandro, Maísa; Almeida Guimarães, Vinícius Henrique; Cassiano, Carolina; Costa-Madeira, Juliana Cristina; Piantino Marques, Anna Laura; Motta, Clara; Silva, Marcos Vinícius; Rodrigues Jr, Virmondes; Francisco Rodrigues, Wellington; Freire Oliveira, Carlo José (Revista de Patologia Tropical / Journal of Tropical Pathology, 2021)
This was a cross-sectional, anonymous, online survey aimed at assessing the perceptions and basic knowledge of COVID-19, a highly transmissible disease caused by SARS-CoV-2, in a sample population in the Triângulo Mineiro region, Minas Gerais, Brazil. A questionnaire devised by the researchers and distributed through social media was applied between June 16, 2020 and August 21, 2020. The survey consisted of questions about the basic aspects of COVID-19, which included symptoms, risk groups, suspicion of infection, prevention, transmission, and perception regarding social isolation. The average distribution, frequencies, similarities and differences between the responses for the different variables were evaluated. Five hundred twenty valid responses were obtained from participants aged ≥18 years. Most of the respondents showed satisfactory basic knowledge of COVID-19. Moreover, the data showed that the participants scored an average of 87.6%. Sex, age, and socioeconomic vulnerability presented a statistically significant link with knowledge of the disease; women, young participants, and the least socioeconomically vulnerable had the highest scores. This study indicated that the population in the Triângulo Mineiro region able to access social networking platforms were basically well informed regarding COVID-19, although differences were observed depending on the group analyzed. KEY WORDS: Coronavirus; knowledge; surveys and questionnaires.